MUTANT IDH1-DRIVEN CELLULAR TRANSFORMATION INCREASES RAD51-MEDIATED HOMOLOGOUS RECOMBINATION AND TEMOZOLOMIDE (TMZ) RESISTANCE. - Pieper, Russell O. (Oxford University Press, 2014)
BACKGROUND: IDH1 mutation is noted in roughly 75% of all lower-grade glioma and is considered to be an early and driving event in the genesis of these tumors. In clinical studies IDH1 mutation correlates with increased overall survival, progression-free survival, and upfront response to TMZ implying that mutant IDH1 directly contributes to drug sensitivity. IDH1 mutant gliomas, however, have a different underlying biology than comparable IDH1 WT glioma, complicating any analysis of the contribution of IDH1 mutation to drug sensitivity. To more accurately determine if and how IDH1 mutation alters drug sensitivity, we employed a system widely for the study of cellular transformation and IDH biology. In this system normal human astrocytes immortalized by introduction of virally-encoded E6, E7 and hTERT can be transformed by additional expression of oncogenic H-Ras or by mutant IDH1, the latter of which induces epigenetic changes similar to those noted in lower-grade glioma. We therefore used these cells to determine if mutant IDH1 expression and/or the transformative events it sets in place were sufficient to alter TMZ sensitivity. METHODS: E6/E7/hTERT-immortalized, untransformed human astrocytes, and the same cells transformed by prior introduction of oncogenic V12H-Ras, were infected with lentiviral constructs encoding WT or mutant (R132H) IDH1, then monitored for transformation status and, following TMZ exposure (100 uM, 3hrs), for DNA damage and repair, cell cycle response, and TMZ sensitivity. RESULTS: The TMZ-sensitive immortalized, untransformed parental cells exhibited DNA damage (H2AX foci) and a prolonged G2 cell cycle arrest that began 2 days after TMZ exposure and persisted for 5 days. The same cells transformed by mutant IDH1 exhibited the same levels of initial DNA damage and cell cycle arrest as controls, although both events resolved significantly faster in the IDH1 mutant cells in association with increased clonagenic survival. The increases in DNA damage processing, cell cycle progression, and clonagenicity were unique to cells transformed by mutant IDH1, and were not noted following introduction of mutant IDH1 into Ras-transformed or established GBM cells. The changes were, however, associated with increased homologous recombination (HR) and could be reversed by the genetic suppression of Rad51, the rate limiting protein in HR. CONCLUSIONS: Mutant IDH1 drives a unique set of transformative events that indirectly enhance HR and increase repair of TMZ-induced DNA damage and TMZ resistance. Inhibitors of HR may therefore be a viable means to further enhance TMZ response in IDH1 mutant glioma. SECONDARY CATEGORY: Preclinical Experimental Therapeutics.